REPRESENTATION OF ERYTHROCYTES IN PIGLET (Sus scrofa) POST HYPOVOLEMIC SHOCK WITH NORMO AND HYPERVOLEMIA RESUSCITATION OF CRYSTALLOID FLUID - Gunanti, Gunanti; Amin, Ahmad Arif; Pudjiadi, Antonius H.; Hayati, Najma (Jurnal Kedokteran Hewan, 2020)
The aim of this study is to evaluate the representation of erythrocytes, which is the count of erythrocytes; hemoglobin concentration, hematocrit value, and platelet count in piglet (Sus scrofa) after hypovolemic shock with normal and hypervolemia resuscitation of crystalloid fluid. This study uses nine male castrated piglets 6-8 weeks of age. The piglets are given treatments such catheter installation, shock induction, normovolemia resuscitation, and hypervolemia resuscitation. The fluid for resuscitation is crystalloid fluid, NaCl 0.9%. Blood sample is taken in baseline, normovolemia condition, and hypervolemia condition. The sample is analyzed using hematology blood analyzer and is tested using T-Paired. Total erythrocytes count after normovolemia resuscitation is 3.07x106/L, while after hypervolemia resuscitation the erythrocytes count decrease until 2.86x106/L. Hemoglobin concentration after normovolemia resuscitation is 9.4 g/dL, while after hypervolemia resuscitation hemoglobin concentration decreases to 8.64 g/dL. Hematocrit count from piglets after normovolemia resuscitation is 28 %, while it decreases after hypervolemia resuscitation to 25.89%. Platelet count after normovolemia resuscitation is 297.22x103/mm3 and decreases to 263.89x103/mm3 after hypervolemia resuscitation. Evaluation of the erythrocytes index shows that the piglets suffer anemia. Hypovolemic shock and normal, and hypervolemia resuscitation cause the significant decreases in all erythrocytes indexes except the platelet count.